Simulasi Perpindahan Panas Pada Pipa Secondary Super Heater (SSH) PLTU 600 MW dengan CFD - Gugum Gumilar; Tarsisius Kristyadi (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
The boiler is an important unit in the PLTU in which there is a Superheater to heat the steam so that increase and becomes superheated steam. The problem is secondary superheater pipe bursts due to excessive heat due to the deposit of the oxide layer in it. This study aims to simulate heat transfer in SSH pipes. with Computational Fluid Dynamics, 3 models are made, without a blockage, blockage at the end, and blockage in the middle. The simulation in a steady state, boiler operational data ; pressure, temperature, velocity flow and mass flow rate. The results show different color profiles for temperature, flow velocity and pressure for the steam and for flue gas. Flue gas heat transfer rate is higher around 800,000 kW, and steam is around 80 kW, Steam mass flow rate is 0.046 kg/s while in the flue gas area it is 0.130 kg/s. The average steam flow rate is around 1 m/s, the maximum is 12 m/s in blocked pipe models, Flue gas flow rate is around 9 to 10 m/s. The average steam temperature is 600°C, and 800°C to 900°C. Steam pressure constant in 16,000,000 Pa and flue gas pressure is 100,000 Pa.